2018
DOI: 10.1002/ejsp.2355
|View full text |Cite
|
Sign up to set email alerts
|

Cultural identity dynamics: Capturing changes in cultural identities over time and their intraindividual organization

Abstract: Important life transitions – such as migration – have the potential to enrich one's sense of self, but they are also demanding and challenging. The current research investigates how cultural identities change and become configured over time among newly arrived international students and the social factors that predict these longitudinal changes. A four‐wave longitudinal study was conducted during international students' first year in their new country (N = 278). Multivariate hierarchical linear modeling analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 75 publications
1
30
1
Order By: Relevance
“…In a study in Canada, higher perceived discrimination predicted lower dual identity integration through greater stress, whereas lower discrimination was related to lower stress and thereby to greater identity integration (Yampolski & Amiot, ). Further, results of a four‐wave longitudinal study among newly arrived international students showed that greater discrimination led to the predominance of one identity over others (Amiot, Doucerain, Zhou, & Ryder, ). Discrimination and rejection from members of the host country can make it harder for immigrants to acquire a new national identity (e.g., Bobowic, Martinovic, Basabe, Barsties, & Wachter, ; Wiley, Lawrence, Figueroa, & Percontino, ).…”
Section: Group Dynamics Associated With Multiple Identitiesmentioning
confidence: 99%
“…In a study in Canada, higher perceived discrimination predicted lower dual identity integration through greater stress, whereas lower discrimination was related to lower stress and thereby to greater identity integration (Yampolski & Amiot, ). Further, results of a four‐wave longitudinal study among newly arrived international students showed that greater discrimination led to the predominance of one identity over others (Amiot, Doucerain, Zhou, & Ryder, ). Discrimination and rejection from members of the host country can make it harder for immigrants to acquire a new national identity (e.g., Bobowic, Martinovic, Basabe, Barsties, & Wachter, ; Wiley, Lawrence, Figueroa, & Percontino, ).…”
Section: Group Dynamics Associated With Multiple Identitiesmentioning
confidence: 99%
“…In Study 2, mainstream categorization was not correlated with either well-being factors whereas heritage categorization was correlated to emotional blending. As previously observed in past literature (Amiot et al, 2018;Yampolsky et al, 2013Yampolsky et al, , 2016, the associations between categorization configurations and well-being remain inconsistent. Additionally, one discordant result was found across the studies, which pertained to the relationship between mainstream and heritage categorization.…”
Section: Discussionmentioning
confidence: 79%
“…From a developmental perspective, the self and the identities that compose it develop over time (Harter, 1999). Certain life stages (e.g., immigration, parenthood) contribute to shaping cultural identities configurations and how they predict well-being (Amiot, Doucerain, Zhou, & Ryder, 2018). Here, we investigate whether attendance at university, compared to postsecondary college-a stage called CEGEP that takes place before university in the province of Qu ebec in Canada and which differs from university (i.e., in terms of age range, size of the student population)has different implications for identity configurations and their associations with well-being.…”
Section: Stage Of Academic Developmentmentioning
confidence: 99%
“…For those who study the process of acculturation among immigrants or sojourners, such as, for example, international students, it may be important to understand that, just as people may identify simultaneously with more than one culture (Oetting et al, 1998), they may internalize their unique or multiple cultural identities for different reasons. When such internalization is more autonomous, however, it is more likely to be accompanied by wellbeing, whether the culture is one's heritage culture, as it was for participants in the three samples reported herein, or, by extension, whether the culture is some other culture to which one has been exposed through choice or circumstance (Amiot, Doucerain, Zhou, & Ryder, 2018;Chu, 2015;Yang, et al, 2018). The acculturation literature typically looks at cultural identity or, alternatively, cultural identification.…”
Section: Discussionmentioning
confidence: 98%